The Global Fisheries Subsidies Divide Between Small- and Large-Scale Fisheries - Schuhbauer, Anna; Skerritt, Daniel J.; Ebrahim, Naazia; Le Manach, Frédéric; Sumaila, U. Rashid (Frontiers in Marine Science, 2020)
In 2015 the Sustainable Development Goals of the United Nations stipulated that certain forms of subsidies that the fishing sector receive must be prohibited. However, the global fishing sector is complex and varied, and as such there remains a need for information on the distribution of subsidies between the different regions and their sub-sectors. This bottom-up study therefore provides up-dated and improved analyses of the financial support fishing sub-sectors receive from public entities. Estimates show that of the USD 35.4 billion of global fisheries subsidies provided in 2018, 19% went to the small-scale fishing sub-sector (SSF), including artisanal, and subsistence fisheries. Whilst more than 80% went to the large-scale (industrial) fishing sub-sector (LSF). Analysis by subsidy category and type shows, for example, that the majority of the subsidies that the LSF receive are in the form of capacity-enhancing subsidies (USD 18.3 billion) with fuel subsidies being the highest overall subsidy type (USD 7.2 billion). Fuel subsidies are especially harmful as they perpetuate fuel inefficient technology. Since the last estimate of the global fisheries subsidies divide, the percentage of capacity-enhancing subsidies within the SSF has increased from 41% in 2009 to 59% in 2018. When assessing the level of subsidization per active fisher at the global scale, a fisher involved in LSF receives disproportionally (3.5 times) more subsidies than a fisher involved in SSF and in terms of subsidies per landed value LSF receive twice as many subsidies per dollar landed than SSF. This unequal distribution of government support exacerbates the ongoing political and economic marginalization of SSF, globally. The Sustainable Development Goals and the supporting science are quite clear, we must remove all capacity-enhancing subsidies across all sub-sectors and regions which exacerbate overcapacity and overfishing, in order to ensure the sustainability of our fish stocks. Our recommendation is that capacity-enhancing subsidies be removed and instead used to support fishers through coastal fishing community projects that focus on fisheries sustainability, social justice and food security, rather than on reducing the cost of fishing or artificially enhancing profits through the provision of harmful subsidization.